LEARNING CELL METHOD (LCM) FOR THE TENTH GRADE STUDENTS OF SENIOR HIGH SCHOOL PALEMBANG IN PROMOTING THE STUDENTS’ ENGLISH ACHIEVEMENT - Asti Veto Mortini (Universitas PGRI Palembang, 2021)
The aim of this study was to find out whether or not study was to find out whether using the learning cell method in teaching narrative text was effective or not to improve the students’ reading comprehension achievement of the tenth-grade students of Karya Ibu Senior High School of Palembang. Thi study applied pre-experiment method. The population of this study was all of the tenth grade students of Karya Ibu Senior High School of Palembang, in the Academic Year 2020/2021 with total number 120 students and 30 students were taken as sampl. In collecting the data, a written test of narrative texts was used, and the data were analyzed by using KR-21 The result of this study showed the students’ mean score in the post-test and pre-test of the test, the matched ttest calculation showed that the value of t-obtained was 21.12. The value of t-table was 1.699. It could be concluded that the value of t-obtained (21.12) was higher than the value of t-table. Then the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It means that teaching narrative texts through Learning Cell method to promote the students’ reading comprehension achivement of the tenth grade students of Karya Ibu of Palembang was effective. Keywords: Teaching, Narrative Text, Learning Cell method.